Acute Exposure to Branched-Chain Amino Acids (BCAAs) Impairs Glucose Homeostasis by Promoting Insulin Resistance in Mice. (14th June 2022) - Gannaban, Ritchel; Shah, Harsh; Shin, Andrew
Abstract: Objectives: Increased plasma BCAAs are associated with T2D. Current evidence suggests that high BCAAs are detrimental to insulin action and glucose metabolism. Chronic supplementation of BCAAs results in development of insulin resistance whereas dietary restriction of BCAAs improves insulin sensitivity and glucose uptake. While these studies indicate a detrimental impact of long-term use of BCAAs, whether BCAAs can acutely contribute to glucose dysregulation and insulin resistance is not understood. Therefore, we tested the role of acutely elevated BCAAs in glycemic control and insulin sensitivity. Methods: 8-week-old C57Bl/6 mice on BCAA or vehicle-treated groups fed a normal chow diet underwent jugular catheter implantation. To determine the acute effects of BCAAs, after 2-hr fast, mice were infused with 150mM BCAAs or 0.9% saline solution through the catheter followed by a frequent glucose monitoring and blood sampling for 30 min for assessment of plasma BCAA and insulin levels. Furthermore, hyperinsulinemic-euglycemic clamps, a gold-standard method for assessing insulin sensitivity, were conducted along with raised plasma BCAAs by continuous infusion. Blood glucose was monitored at every 10 min for 120 min, and a variable rate of glucose was infused to maintain euglycemia. Blood glucose was checked by a hand-held glucometer, and plasma BCAAs and insulin were measured by enzymatic and ELISA assays, respectively. Whole-body insulin sensitivity during clamps was determined by glucose infusion rate (GIR). Results: Jugular infusion of BCAAs, but not vehicle, acutely elevated plasma BCAAs that was maintained for 30 min. Whereas vehicle-treated controls did not display any changes from baseline, BCAA-infused mice acutely raised blood glucose by 20% in spite of increasing and maintaining plasma insulin, indicative of possible insulin resistance. This was supported by a significantly lower GIR, an accurate readout of whole-body insulin sensitivity, in mice with an acute, sustained elevation of plasma BCAAs compared to vehicle-treated mice during hyperinsulinemic-euglycemic clamps. Conclusions: These findings suggest that BCAAs can acutely disturb glucose homeostasis and insulin action. Future studies will aim to determine the underlying mechanisms for BCAA-induced metabolic dysregulation. Funding Sources: NIH R21 AG069140-01; Diabetes Action Foundation